The influence of microfinance factors on entrepreneurial competencies and business success among women entrepreneurial in Kelantan: a case study of Sahabat Amanah Ikhtiar Malaysia in Kelantan - Mohamad Hanif Baharudin
Problem statement: Malaysian government i currently pushing and encouraging for women involvement in entrepreneurship, which will ultimately stimulate the country's economy. Furthermore, concerns regarding the survival and sustainability of business and women entrepreneurs have been brought up by the leadership, despite governmental recognition. The journey towards business success among these women entrepreneurs, especially those from developing countries, may be further com heated by the lack of competencies and the need for continuous assistance. Thus, the pr t study is aiming to propose a model for women business succes , aligning with the rol of rnicrofinance (as a continuous assistant) and entrepreneurial competencies. Methodology: A total of 392 women entrepreneur under the Amanah Ikhtiar Malaysia (AIM) scheme from Kelantan have been involved in this study. It has utilised 6 dimensions of entrepreneurial comp tencies, which are: strategic ompetencies, commitment competencies, organizing competencie, relationship competencies, commitment competencies, opportunity competencie and conceptual competencies. Meanwhile, microfinance factors like the financial factor and non-financial factor has been used as a moderating effect, whereby their respective dimensions are credit and saving and social capital and training accordingly. Structural Equation Modeling (SEM) ha been employed as the main statistical technique in this study. Results: Overall, the study ha found that only four of the independent variables (i.e. elements of entrepreneurial competencies), namely relationship, opportunity, organizing and commitment competencies have significant relationships with women's business success. The remaining 2 domains, strategic competencies and conceptual competencies have revealed to be not significant. Furthermore, the financial factors fully moderated the relationship between entrepreneurial competencie and business success, whereas the non-financial factors have posed partially moderating effect. Conclusion: The findings are likely to be useful to SMEs, as they have highlighted the necessity of focusing on training to yield increased effectiveness. In addition, the impact of microfinance factors will assist women entrepreneurs to becoming successful in their businesses. The model from this study will also further contribute towards the development of literature review related to the favourable outcome for women entrepreneurs.